The human spark - Alda, Alan 1936-; Chedd, Graham; Engel, Larry (PBS Distribution, 2009)
Alan Alda takes a look at how humans first appeared on Earth millions of years ago, and how our species not only survived, but thrived, through some unimaginable conditions. Alda visits with dozens of scientists on three continents, and participates directly in many experiments - including the detailed examination of his own brain.